2015
DOI: 10.1002/hep.28284
|View full text |Cite
|
Sign up to set email alerts
|

Liver capsule: Age‐influenced hepatic immune priming determines HBV infection fate: Implications from mouse to man

Abstract: Abbreviations CXCL13chemokine (C-X-C motif) ligand 13

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The age range of enrolled subjects may be one of the reasons for the consistency. The fate of HBV infection could be determined by age‐influenced hepatic immune priming 18 . Patients who were included in our study were aged 13–82‐years old, while the individuals in the previous epidemiological investigation were 1–59 years old 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age range of enrolled subjects may be one of the reasons for the consistency. The fate of HBV infection could be determined by age‐influenced hepatic immune priming 18 . Patients who were included in our study were aged 13–82‐years old, while the individuals in the previous epidemiological investigation were 1–59 years old 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The fate of HBV infection could be determined by age-influenced hepatic immune priming. 18 Patients who were included in our study were aged 13-82-years old, while the individuals in the previous epidemiological investigation were 1-59 years old. 6 We observed that the prevalence of anti-HBc increased with age, which is consistent with several epidemiological studies in the general people in China.…”
Section: Discussionmentioning
confidence: 99%
“…The young mice developed strikingly weak HBV-dependent inflammatory responses compared with adult mouse recipients. Mechanistically, these studies found that higher HBV-dependent IL-21 production, lymphoid organization facilitated by hepatic macrophages, and immune priming in adult mouse livers may play pivotal roles in determining age-dependent immune response potency upon HBV infection [ 118 , 119 , 120 ].…”
Section: Non-infection Murine Modelsmentioning
confidence: 99%
“…1 It is widely accepted that the virus-host interaction, which is affected by age, transmission route, immune status and other factors, determines the outcome of infection. 2,3 Both adaptive and innate immunity are involved in anti-HBV immune response. On one hand, antigen-presenting cells (APCs), including macrophages and dendritic cells (DCs), initialize the virus-specific adaptive immunity characterized by activation of T helper lymphocytes and secretion of various cytokines, which then mobilize the cytotoxic T lymphocyte (CTL) to kill the HBV-infected cells.…”
Section: Introductionmentioning
confidence: 99%
“… 1 It is widely accepted that the virus-host interaction, which is affected by age, transmission route, immune status and other factors, determines the outcome of infection. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%